2016
DOI: 10.1103/physreve.93.013110
|View full text |Cite
|
Sign up to set email alerts
|

Power-exponential velocity distributions in disordered porous media

Abstract: Velocity distribution functions link the micro- and macro-level theories of fluid flow through porous media. Here we study them for the fluid absolute velocity and its longitudinal and lateral components relative to the macroscopic flow direction in a model of a random porous medium. We claim that all distributions follow the power-exponential law controlled by an exponent γ and a shift parameter u_{0} and examine how these parameters depend on the porosity. We find that γ has a universal value 1/2 at the perc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 32 publications
8
31
0
Order By: Relevance
“…As the porosity increases, the distribution approaches a stretched exponential function for large v , p()truev̂exp()αtruev̂β where truev̂=v/〈〉v, the exponent β ≃1/2, and the scale parameter α ≃0.25. This observation is consistent with established velocity statistics for disordered porous media [ Matyka et al , ], and the stretched exponential distribution can theoretically be inferred by considering the porous media as a collection of cylinders with exponentially distributed radii [ Holzner et al , ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As the porosity increases, the distribution approaches a stretched exponential function for large v , p()truev̂exp()αtruev̂β where truev̂=v/〈〉v, the exponent β ≃1/2, and the scale parameter α ≃0.25. This observation is consistent with established velocity statistics for disordered porous media [ Matyka et al , ], and the stretched exponential distribution can theoretically be inferred by considering the porous media as a collection of cylinders with exponentially distributed radii [ Holzner et al , ].…”
Section: Resultssupporting
confidence: 87%
“…With regard to the speed distributions presented in section 3, a stretched exponential probability density function provides a good fit for large speeds. A shifted, stretched exponential (power exponential) distribution, as proposed by Matyka et al [], would also be in agreement with our results, but this would require introducing another fitting parameter. Moreover, the evolving pore structure due to dissolution in our sample does not significantly alter the functional dependence of the probability density function of fluid velocities, when rescaled by the average velocity.…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon is responsible for incomplete mixing or enhanced spreading, persistently spanning scales from the pore to the field (Berkowitz et al, ; Dentz et al, ; Edery et al, ; Gouze et al, ; Le Borgne et al, ; Le Borgne & Gouze, ). At the pore scale, anomalous transport exhibits many different characteristics such as non‐Gaussian velocity distributions (Bijeljic et al, ; Matyka et al, ), high temporal correlation of Lagrangian velocities forming a spatial Markov process (Le Borgne et al, ), intermittency of velocities along trajectories (de Anna et al, ), and superdiffusive spreading (Holzner et al, ; Kang et al, ). The intensity of the anomalous transport is related to the heterogeneity of the porous medium and has been investigated in media of different complexities, ranging from simple beadpacks to fractured sandstones and carbonates (Bijeljic et al, ; Meyer & Bijeljic, ; Morales et al, ; Siena et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental and numerical studies have shown that the occurrence of non‐Fickian particle dispersion due to long advective residence times is directly linked to intermittency in the Lagrangian velocity time series (Carrel et al, ; De Anna et al, ; Holzner et al, ; Kang et al, ; Morales et al, ). Thus, the understanding of these phenomena requires a sound characterization and understanding of the dynamics of Lagrangian and Eulerian pore‐scale velocities, which have been the subject of a series of recent studies (De Anna et al, ; Gjetvaj et al, ; Holzner et al, ; Jin et al, ; Meyer & Bijeljic, ; Morales et al, ; Matyka et al, ; Siena et al, ).…”
Section: Introductionmentioning
confidence: 99%